(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
In order to improve nitrogen fertilizers application recommendations for cereals, the soil mineral nitrogen (Nmin) investigations (1995 – 2000) were carried out on sod – podzolic and brown – lesssive loamy sand and loamy soils in co-operation with other research institutions. The soil samples for determination of NO3 – N and NH4 – N were taken in depth 0 - 20, 21 – 40 and 41 – 60 cm in spring before the start of growth on winter cereals fields, but in 2001,2002- also in autumn before the sowing of winter cereals. Data on soil properties, the amount of precipitation in autumn (August 1 until the first decade with the average temperature below 5 oC), preceding crops and the use of organic fertilizers at sites of investigations were considered. The determination of NO3 – N and NH4 – N content was carried out in wet soil samples using for extraction 1 M KCl. Statistical analysis of data obtained in spring has been carried out using MS EXCEL function CORREL, CORRELATION, REGRESSION and SPSS 8.0 for Windows (GLM procedure). According to this analysis the following model (R2 = 0,527) was elaborated: y = 103.513 – 13.515|X1=1 – 0.247·X3 – 27.069|X2=0 – 42.945|X2=1 – 39.044|X2=2 – 16.022|X2=3 – 44.212|X2=4 + 0.104·X3|X2=0 + 0.181·X3|X2=1+ 0.187·X3|X2=2 +0.117·X3|X2=3+0.175·X3|X2=4, where y- predicted Nmin content in spring in 0- 40 cm soil layer, kg ha-1; 103.513 – intercept; X3 – amount of precipitation in autumn, mm; X1 – soil texture; X1=1 – loamy sand soils, X2 – predecessor; X2=0 – cereals; X2=1 – perennial grass; X2=2 – tilled crops; X2=3 – legumes; X2=4 – green manure crops; X2=5- fallow. On the basis of this model and data on meteorological conditions at different sites of Latvia the recommendations on correction N top - dressing application rates for winter cereals in spring were prepared.